Left atrial appendage closure using WATCHMAN device in chronic kidney disease and end‐stage renal disease patients. Issue 7 (9th June 2022) - Jamal, Shakeel; Mughal, Mohsin Sheraz; Kichloo, Asim; Edigin, Ehizogie; Khan, Muhammad Zia; Minhas, Abdul Mannan Khan; Ali, Muzaffar; Kanjwal, Khalil
Abstract: Background: Chronic kidney disease (CKD) and end‐stage renal disease are considered independent risk factors for developing atrial fibrillation (AF). Percutaneous occlusion of left atrial appendage (LAAC) using WATCHMAN device is a widely accepted alternative to anticoagulation therapy to prevent ischemic stroke in AF in patients who are not candidates for anticoagulation. There is limited data regarding the utilization and periprocedural safety of this intervention in patients with CKD/ESRD. Methods: We retrospectively reviewed all hospitalizations from 2016 to 2017 with (ICD‐10) procedure diagnosis code of LAA closure using WATCHMAN procedure with and without a secondary diagnosis of CKD/ESRD in acute‐care hospitals across the United States using the national inpatient sample. Demographic variables (gender, race, income, hospital characteristics, medical comorbidities) were collected and compared. The primary outcomes were inpatient mortality, hospital length, and cost of stay. Results: There were over 71 million discharges included in the combined 2016 and 2017 NIS database. Sixteen thousand five hundred five hospitalizations were for adult patients with a procedure code for LAA closure via watchman procedure. Of 16, 505 patients, 3245 (19.66%) had CKD and ESRD. There was no statistically significant difference in mortality, length, and cost of stay in patients with and without CKD/ESRD. There were no statistically significant differences in periprocedural cerebrovascular accidents in both groups. Conclusion: Patients with and without ESRD/CKD who undergo LAA occlusion with Watchman have similar procedure related, in‐hospital mortality, and complications.